The nature of the current social security system of the United States and a comparison with the social security system of the Czech Republic - Rejka, Martin; Prachař, Ondřej; Štěpánek, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2013)
The main objective of this paper is an analysis of the US social security system. The American social security system is much less generous than European systems. The hypothesis that I test in this paper is that the level of redistribution in the US is low because people's demand for it is low. Economical models suggest three main groups of explanations - economical, behavioural and political. Economical explanations are the weakest of the three, often providing contradictory results. Discrimination, rooted in the vast racial heterogeneity of the US, along with the electoral system are the most convincible explanations. The secondary objective is a practical comparison of the US' social security system with the system established in the Czech Republic and a suggestion of the possible improvements. Both systems show high level of oppositeness and apart from the health care system, there is very little to be applied from one system in the other one.
Vedoucí práce: Ondřej Prachař
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: národní hospodářství [obor bakal. práce]; bakalářské práce; bachelor's theses